Efisiensi Model Fisik Peredaman Energi Gelombang Dengan Permeable Breakwater - Juventus Welly Ginting (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
In this research calculates the efficiency of wave energy reduction by using permeable breakwater as an alternative coastal protection. The method used is to do physical modeling in the laboratory to get optimal efficiency. The preparation of the model scenario is done by changing the schematization of the model scenario by changing the permeable brackwater characteristics (width b and height h) to the water level d. and the T wave period. Wave energy is calculated at the location in front of the structure and behind the structure. After calculating the comparison of wave energy in the two locations, it can be obtained the efficiency value of wave energy reduction due to the existence of the structure. The influence of the structure dimension on the reduction of the highest wave energy is obtained with the highest energy reduction value when the condition h / B = 1 where the condition of the structure is the same as the width of the structure. In the conditions of damping the wave energy when compared to the water depth (d) the greatest energy reduction value is at d = 10 cm so that in its utilization as a wave energy damper the height of the structure must be higher than the mean Mean level level (MSL) in the area to be applied structure permeable breakwater will be placed.